Patterns of leukemia incidence in the United States by subtype and demographic characteristics, 1997-2002 - Yamamoto, Jennifer F; Goodman, Marc T (Cancer causes & control, 2008)
Objective Efforts to prevent leukemia have been hampered by an inability to identify significant risk factors. Exploring incidence patterns of leukemia subtypes by sex and race/ethnic group may generate new etiologic hypotheses and identify high-risk groups for further study. Methods Data from the North American Association of Central Cancer Registries for 1997-2002 were used to assess patterns of leukemia incidence by subtype, sex, age, race and ethnicity. Results A total of 144,559 leukemia cases were identified, including 66,067 (46%) acute and 71,860 (50%) chronic leukemias. The highest rates of acute myeloid leukemia with and without maturation were observed in Asian-Pacific Islanders (API). Hispanics had a higher incidence of acute lymphocytic leukemia, particularly in childhood, and promyelocytic leukemia than did non-Hispanics. African-Americans had the highest rates of HTLV-1 positive adult T-cell leukemia/lymphoma. A sharp increase in the incidence of chronic myeloid leukemia was observed for both APIs and Hispanics, 85 years and older. Conclusion Known risk factors are unlikely to explain the observed disparities in leukemia incidence. Further studies of differences in environmental and genetic risk factors in these populations by specific leukemia subtype may provide clues to the etiologies of these malignancies.